Operations management of private educational institutions - Buenviaje, Jerome T. 1980- (2009)
The transformation functions of Operations Management and the actual practice of these functions in the private educational institutions were examined. The study used quantitative approach through a cross-sectional survey design to a total of 103 respondents composed of administrators, teachers and staff of selected private schools in Region 4-A. Results showed that all transformation functions of Operations Management presented were apparently applicable in private school operations and were regularly practiced. There was a positive effect of Operations Management functions to school performance in terms of student retention and teacher retention rates.